(3JGQjN GdSGOI GdYdeGA Gdced GdfHdGA GdaVdGA (B( (3Hfi GdhRjQ(B)s - (3CMeO Hf YHO Gddg Hf CMeO Hf EHQGgje Hf Ydj Hf GdeQJVj, GHf GdhRjQs
(3ChdgG (B:s
(3GdMeO ddg GdPi CSHZ YdjfG fYeg HGWfg hXGgQI s
(3BNQgG (B:s
(3GfJgi cdGe SjOi LeGd GdOjf QMeI Gddg Ydjg s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B73 s
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(3684(1)) s
Keywords: (3GdJGQjNs